Find the value of α such that:
4 x 2 − 4 x + 6 + ( 3 α + 2 ) y 2 − 6 α x y − 4 y ≤ 0
for x , y satisfying the inequality where x , y ∈ R .
You can try more of my fundamental problems here .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hmm, I think you might want to reword your problem, especially the "for all reals x , y " part, because one might think you meant the inequality 4 x 2 − 4 x + 6 + ( 3 α + 2 ) y 2 − 6 α x y − 4 y ⩽ 0 holds for some value α (which they have to find) no matter what real value x and y they choose, hence when they see this problem, they might try setting y = 0 to get 4 x 2 − 4 x + 6 ⩽ 0 , which is impossible, and thus get stumped.
Log in to reply
So I should add that y = 0 to remove the clouds of doubt is it?
Log in to reply
You could just ask to find a real α such that x , y satisfy the inequality, where x , y ∈ R .
Problem Loading...
Note Loading...
Set Loading...
4 x 2 − 4 x + 6 + ( 3 α + 2 ) y 2 − 6 α x y − 4 y ≤ 0
3 ( α y 2 − 2 α x y + x 2 ) + ( x 2 − 4 x + 4 ) + 2 ( y 2 − 2 y + 1 ) ≤ 0
3 ( α y − x ) 2 + ( x − 2 ) 2 + 2 ( y − 1 ) 2 ≤ 0
However,
( α y − x ) 2 ≥ 0
( x − 2 ) 2 ≥ 0
( y − 1 ) 2 ≥ 0
∴ 3 ( α y − x ) 2 + ( x − 2 ) 2 + 2 ( y − 1 ) 2 ≥ 0
There is solution if and only if the equality holds.
When 3 ( α y − x ) 2 + ( x − 2 ) 2 + 2 ( y − 1 ) 2 = 0
⎩ ⎪ ⎨ ⎪ ⎧ α y − x = 0 x − 2 = 0 y − 1 = 0
x = 2 , y = 1
∴ α ⋅ 1 − 2 = 0
α = 2
∴ α = 4